Circulating Irisin Concentrations Are Associated with a Favourable Lipid Profile in the General Population. - Simon Oelmann; Matthias Nauck; Henry Völzke; Martin Bahls; Nele Friedrich (PLoS ONE, 2016)
Irisin is a myokine, which is mainly inversely associated with the risk for non-communicable diseases. Irisin improves cellular energy metabolism by uncoupling the mitochondrial respiratory chain resulting in increased energy expenditure using lipids. To date potential associations between irisin concentration and lipid profile are poorly understood. Therefore, this investigation aimed to evaluate potential associations between irisin and lipid levels in the general population.Data of 430 men and 537 women from the population-based Study of Health in Pomerania (SHIP-TREND) with available irisin and lipid concentrations were used. Analyses of variance, linear and logistic regression models adjusted for age, HBA1c, waist circumference, physical activity, smoking, alcohol consumption, systolic blood pressure, ALAT were calculated.We detected significantly inverse associations between irisin and circulating levels of total [beta coefficient 0.21 (standard error 0.08), p = 0.01], low-density cholesterol [-0.16 (0.07), p = 0.03] and triglycerides [-0.17 (0.08), p = 0.02] for men. Females without lipid lowering medication had an inverse association between irisin and total cholesterol [-0.12 (0.06), p = 0.05]. Further, male subjects with irisin concentrations in the third tertile had an increased odds for elevated low-density cholesterol [odds ratio 1.96 (95% confidence interval 1.07-3.48), p = 0.03) and triglyceride [1.95 (1.09-3.47), p = 0.02] levels, even after exclusion of subjects with lipid lowering medication. In addition, our data revealed an annual rhythm of serum irisin levels with peak levels arise in winter and summer months.This is the first investigation to report a significant association between circulating irisin and a favourable lipid profile in the general population. This may infer that higher irisin concentrations are associated with a reduced risk for non-communicable diseases.